The Role of Parents in Motivating Class VIII Children's Learning at SMPN 2 Waigete During the Covid 19 Pandemic - Klaver, Petrus; Kepalet, Petrus; Nuwa, Gisela (EDUCTUM: Journal Research, 2022)
Law No. 20 of 2003 concerning the National Education System that education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble character, and skills needed by himself, the community, the nation and the State. Therefore, the role of parents in motivating the learning of class IIA SMPN2 Waigete children during the Covid 19 pandemic is very important for the realization of intelligence and morals in students because parents are a source of hope for children's success in the learning process during the Covid-19 pandemic, causing the learning process from home, different when compared to conventional learning. This study uses a qualitative approach. and descriptive research results obtained in the field that parents carry out two roles at once in order to motivate students during the learning process from home. The first is to be a friend and the second is to be a teacher/educator at home. Even though parents had difficulties in the learning process during the Covid-19 pandemic at SMPN 2 Waigete, the education provided by parents affected the level of ease and difficulty for parents in educating their children; parents' economic level affects the online learning process, especially in terms of facilitating children's online learning to buy data/internet credit, poor network, difficulty dividing time between children and work; The number of family members also influences parents in providing guidance to children in studying at home